Factors affecting breakfast consumption and its association with academic performance among undergraduates / Arimi Fitri Mat Ludin ... [et al.] - Mat Ludin, Arimi Fitri; Lim, Soon Li; Ho, Mei Ting; Chiah, Hui Lin; Wan Ya, Wan Nurhafizi; Kamarul Zaman, Mariah; Gunasekaran, Devathini Dewi; Kamararudin, Nur Izzati; Lim, Min Li; Abdul Razak, Natasha; Tan, Chain Yee; Saidin, Nurliyana; et al. (Universiti Teknologi MARA, Perlis, 2016)
The positive association between breakfast consumption and improved mental health status has been reported in adults. A cross-sectional study was conducted among second year undergraduates of Faculty of Health Sciences, Universiti Kebangsaan Malaysia, Malaysia. Systematic random sampling method was used in selecting the respondents from 10 programmes and a set of questionnaire has been distributed to 180 respondents. Results were analyzed using SPSS version 13.0 software. Factors that significantly affected breakfast consumption and academic performance were environmental factors (p < 0.05) which include the aspects of family background, food choices and accessibility. There is no association between habits of taking breakfast and source of education fund. Academic performance of the respondents was associated with the quantity of breakfast consumed in terms of energy and macronutrient contents.